Glucokinase (GCK) and other susceptibility genes for β-cell dysfunction: the candidate approach. (21st May 2008) - Gloyn, Anna L.; Tribble, Nicholas D.; Bunt, Martijn van de; Barrett, Amy; Johnson, Paul R.V.
Abstract : There are well-documented examples in the literature of where determining the genetic aetiology of a disorder has provided insights into important regulatory pathways and protein interactions, and, more recently, has led to improved treatment options for patients. The studies of monogenic forms of β-cell dysfunction are no exception. Naturally occurring mutations in the gene for the β-cell enzyme glucokinase ( GCK ) result in both hyper- and hypo-glycaemia. Over 200 mutations have been described, and careful study of the mutational mechanisms for a number of these has provided important insights into glucokinase regulation. Increased understanding of post-translational regulatory mechanisms holds the promise of novel pharmacotherapeutic options for the treatment of T2DM (Type 2 diabetes mellitus). It is well established that common genetic variation in genes involved in monogenic forms of β-cell dysfunction contributes to susceptibility to T2DM. Recent genome-wide scans for association have identified a number of novel T2DM susceptibility genes which probably influence β-cell mass and/or function. Their identification allows the investigation of the role of rare mutations in monogenic β-cell dysfunction. Current results indicate the importance of these genes in pancreatic development and suggest that mutations which result in a severe functional defect could be lethal.